SEAFEEDTM: INOVASI PAKAN FUNGSIONAL UNTUK TERNAK RUMINANSIA BERBASIS SELADA LAUT LOKAL SUMBAWA Ulva lactuca (Linnaeus) YANG DIFORTIFIKASI DENGAN PROBIOTIK, PREBIOTIK DAN POSTBIOTIK - Ali Budhi Kusuma; Imam Munandar; Husni; Leggina Rezzy Vanggy (Jurnal TAMBORA, 2022)
Sumbawa Island is included in the Thousand Cow Village program because it has a high potential of cattle reaching more than 738,000 heads in 2020. However, the limited number of quality cattle feed producers in Sumbawa causes local farmers to rely heavily on expensive commercial feed. Alternative uses of forage and fresh grass are also commonly used, but they have the potential to pose a serious threat to the health of the digestive tract of cattle and become the largest contributor to methane gas in the atmosphere. The “SeafeedTM” innovation, is a functional feed product for ruminant livestock made from local Sumbawa sea lettuce from the Ulva lactuca species, a species of green algae with high nutrition which is very abundant in the northern waters of Sumbawa Island and its potential has not been utilized optimally. The protein content which reaches 14% and soluble fiber >45% in Ulva lactuca sea lettuce makes this species a very prospective candidate to be used as a high-quality feed source. The ingredients used are sea celery (Ulva lactuca), bran, premix-porbiotic & prebotik, and molasses. A simple method of manufacture with a mixed composition, namely 10% sea cress, premix-probiotics & prebiotics, 30% molasses and 60% bran. Seafeed is an innovative ruminant feed made from local seaweed from Sumbawa which has complete nutritional content to support the growth of livestock. The content of probiotics, prebiotics, and postbiotics makes this product into the category of functional feed that functions to increase immunity in livestock. It is hoped that this product can be developed commercially to support the ability of farmers on Sumbawa Island to utilize local biological natural resources as feed ingredients so that dependence on commercial feed supplies can be reduced.